Exploring the Impact of the Increased Tuition Fees on Academic Staffs' Experiences in Post-92 Universities: A Small-Scale Qualitative Study - Elizabeth A. Bates; Linda K. Kaye (MDPI AG, 2014)
The introduction of the new tuition fee regime in the UK academic session 2012-2013 has resulted in concerns in the Higher Education (HE) community that students' expectations may become unmanageable. Previous research has explored the expectations and experiences of undergraduate psychology students; the current study extended this by considering whether the increased tuition fees have changed the experiences of academic staff in HE. To achieve this, five semi-structured interviews with psychology staff in two post-92 Higher Education Institutions (HEIs) were undertaken. Results suggested staff perceptions have undergone minimal change in their day-to-day experiences. However, perceptions of the wider HE issues, such as meeting targets and fulfilling requirements of the role, appear to be enhanced following the contextual changes of HE. Finally, the results reported here suggest generally good staff satisfaction, regardless of these changing times within the sector. Future research and the need for more widespread, large scale studies are discussed.